Mengasah Kemampuan Penulisan Laporan Lapangan - Lubis, Desy Irana Dewi; Nazmah (Cattleya Darmaya Fortuna, 2025)
The writing of fieldwork reports (PKL) is a crucial skill in vocational education. However, many vocational high school (SMK) students face challenges in producing well-structured and systematic reports. The government's 2019 Vocational Education Revitalization Program aims to enhance the quality of vocational education, including report writing skills. This community service activity was designed to address this issue by providing report-writing training to 10 SMK students in Deli Serdang. The methods used included initial interviews, interactive training, and evaluation sessions focusing on understanding report structure, effective writing techniques, and data presentation. The training results showed a significant improvement in the student's ability to produce PKL reports that meet academic and professional standards. Additionally, the training helped students develop analytical and critical thinking skills, essential for preparing them for the workforce. This program is expected to serve as a reference for educational institutions in designing similar training to enhance students' report writing quality.